2021
DOI: 10.1021/acsami.1c13117
|View full text |Cite
|
Sign up to set email alerts
|

Conformal and Stoichiometric Chemical Vapor Deposition of Silicon Carbide onto Ultradeep Heterogeneous Micropores by Controlling the Initial Nucleation Stage

Abstract: Conformal chemical vapor deposition (CVD) of silicon carbide (SiC) from methyltrichlorosilane (MTS) and hydrogen (H2) onto high-aspect-ratio (HAR; typically >100:1) three-dimensional features has been a challenge in the fabrication of ceramic matrix composites. In this study, the impact of heterogeneous underlayers on the initial nucleation of SiC-CVD was studied using HAR (1000:1) microchannels with a tailored wetting underlayer of Si(100) and dewetting underlayers of thermally formed amorphous silicon dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Other various studies on CVD and PVD process modeling and numerical simulations have also been reported (Refs. 8995).…”
Section: Deposition Modelsmentioning
confidence: 99%
“…Other various studies on CVD and PVD process modeling and numerical simulations have also been reported (Refs. 8995).…”
Section: Deposition Modelsmentioning
confidence: 99%
“…1) Moreover, advanced complex structures and vertical integration, including fin-type field-effect transistors (FinFET), 2) vertical tunnel FETs, 3) and gate-all-around FETs, 4) have been proposed. Therefore, careful deposition process control [5][6][7][8][9][10][11][12][13][14][15][16][17] for the realization of a high-aspect-ratio (HAR) pattern to consider the coverage and film properties (density, passivation, adhesion, etc. ), both of which greatly affect the device performance, is vital.…”
Section: Introductionmentioning
confidence: 99%